2022
DOI: 10.3389/fonc.2022.966920
|View full text |Cite
|
Sign up to set email alerts
|

A novel cuproptosis-related LncRNA signature: Prognostic and therapeutic value for acute myeloid leukemia

Abstract: BackgroundCuproptosis is a type of programmed cell death that is involved in multiple physiological and pathological processes, including cancer. We constructed a prognostic cuproptosis-related long non-coding RNA (lncRNA) signature for acute myeloid leukemia (AML).MethodsRNA-seq and clinical data for AML patients were acquired from The Cancer Genome Atlas (TCGA) database. The cuproptosis-related prognostic lncRNAs were identified by co-expression and univariate Cox regression analysis. The least absolute shri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Peter Tsvetkov et al [ 7 ] recently described a novel type of cell death called cuproptosis, which is distinct from the known processes of death such apoptosis, pyroptosis, necrosis, and ferroptosis. Cuproptosis has been shown to be associated with the occurrence and development of a variety of cancers, including liver cancer [ 8 ], colorectal cancer [ 9 ], esophageal cancer [ 10 ], and some hematologic malignancies, including the acute myeloid leukemia [ 11 ]. These studies suggest that cuproptosis may be associated with a wider range of malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…Peter Tsvetkov et al [ 7 ] recently described a novel type of cell death called cuproptosis, which is distinct from the known processes of death such apoptosis, pyroptosis, necrosis, and ferroptosis. Cuproptosis has been shown to be associated with the occurrence and development of a variety of cancers, including liver cancer [ 8 ], colorectal cancer [ 9 ], esophageal cancer [ 10 ], and some hematologic malignancies, including the acute myeloid leukemia [ 11 ]. These studies suggest that cuproptosis may be associated with a wider range of malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…The construction of the prognosis prediction model might It should be noted that the use of cuproptosis-related lncRNAs for prognostic prediction has been reported in various cancers, including osteosarcoma [34], colon cancer [25], gastric cancer [35], hepatocellular carcinoma [23], and head and neck squamous carcinoma [36]. A recent study identified four cuproptosis-related lncR-NAs involved in the prediction of the 2-year OS outcomes in AML patients [13]. In the present study, seven cuproptosis-related lncRNAs were utilized in the construction of a prognostic model for 1-, 3-, and 5-year AML prognosis prediction, which showed good prediction performance (all AUC > 0.8).…”
Section: Discussionmentioning
confidence: 99%
“…For example, cuproptosis was used to predict clinical outcomes and immune response in bladder cancer [9], breast cancer [10], colorectal cancer [11], and prostate cancer [12]. A more recent study suggested that cuproptosis-related genes might be critically involved in the 2-year AML prognosis and the immune response to treatment [13]. However, the role of cuproptosis in the pathogenesis and the long-term prognosis of AML has not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Although multiple prognostic factors including leukemia type, age, white blood cell count, cytogenetics, and recurrent mutations have been identified, the outcome prediction and risk stratification in leukemia patients are still not optimal and need improvement. Given lncRNAs' important role in regulating leukemia patient outcome, there are studies to investigate the potential of incorporating lncRNAs to improve the current prediction model for drug resistance and exploiting them as potential targets to overcome therapeutic resistance 98,99 . Indeed, the lncRNA landscape has been characterized in multiple leukemia types and corresponding lncRNA scores have been developed for outcome prediction.…”
Section: Future Perspectives On Lncrna‐based Strategies To Improve Tr...mentioning
confidence: 99%